Assessment of Dyeing Time on Color Change of Dyed Cotton Fabrics using Household Bleach - Braide, Olufunmilayo Olasunmbo; Adeboye, Adebiyi Oladipupo; Labode, Oladoyin Jamiu; Sowemimo, Bukola Olamidun (NIU Journal of Humanities; Vol 9 No 3 (2024): NIU Journal of Humanities, Vol. 9 No. 3, September 2024, 2024)
Dyeing processes play a pivotal role in the textile industry, enabling the patterns context. The duration of dyeing, often referred to as "dyeing time," is an essential variable that impacts color development, color fastness, and resource utilization. The significance of this study is multi fold in textile production. It revealed and addresses a knowledge gap in the textile industry concerning the influence of varying dyeing times on cotton fabrics. The study has multiple fronts that addresses a critical aspect of textile production in the dyeing process. A range of different dyeing times, including short and long durations of 10 minutes to 50 minutes is established. Descriptive Statistic was used to analyse the data which summarizes and describes the characteristics of the data set. This consists of three basic categories of measures: measures of central tendency, measures of variability (or spread), and frequency distribution. Higher dye concentration can reduce the time required for the dye to exhaust onto the fabric. It is apparent that green and purple dyes were used, and the temperature was maintained at 87.5°C. The study examined the parameters for dyeing cotton fabric and assessed the color strength and color parameters of the resulting samples. Beyond this point, dye absorption remained relatively constant, indicating equilibrium in dye absorption. The impact of dyeing time and dye absorption equilibrium, manufacturers can minimize resource wastage.